Legal Issue Comparison of Piracy and Armed Robbery with Emphasis on the South China Sea-Malacca Strait and the Persian Gulf -Strait of Hormuz - Mohammad Ali Zohourian (Fiat Justisia: Jurnal Ilmu Hukum, 2020)
International trading flows have always been the subject of geopolitical risks and conflicts. Different stages of the supply chain, trade always face inherent challenges caused by geopolitical realities along given routes. In this study, the data concerning piracy and armed robberies of ships reported to the Global Integrated Shipping Information System were considered. The statistics include the information on the incidents during the period between 1998 and 2018 on different types of ships, in two most strategic areas, namely the South China Sea (SCS) and the Strait of Malacca (area 1) and the Strait of Hormuz and the Persian Gulf (area 2). According to the GISIS reports, most of the incidents occurred in the South China Sea and the Strait of Malacca are respectively 1684 and 610. Because of the importance of both the Strait of Hormuz and the Malacca Strait as the most vital waterway in the world, it is necessary to have a clear picture of the security situation in the two aforementioned Strait. This research allowed us: 1) to make a distinction between the security in two aforementioned areas; 2) to represent the source of the information for researchers.